Evaluation of Upper Paleozoic source rocks in the southeastern margin of the Ordos Basin - Wan, Yongping; Wang, Zhenchuan; Cui, Minrui; Liu, Kouqi; Li, Wu (Frontiers in Earth Science, 2025)
IntroductionThe Yanchang gas field in the southeastern Ordos Basin is an important region for natural gas exploration due to the presence of Upper Paleozoic coal-bearing source rocks. This study systematically evaluates these source rocks in terms of organic matter abundance, type, and thermal maturity to assess their hydrocarbon generation potential.MethodsOrganic geochemical analyses were performed to determine the total organic carbon (TOC) content, kerogen type, and thermal maturity of the source rocks. The Benxi and Taiyuan Formations were specifically targeted for detailed evaluation. Kerogen maceral analysis was used to classify organic matter types, while thermal maturity was assessed through vitrinite reflectance (Ro) values.ResultsThe results indicate that the Upper Paleozoic source rocks exhibit high TOC content, with the Benxi and Taiyuan Formations showing excellent hydrocarbon generation potential. Kerogen maceral analysis identified predominantly Type III (humic) kerogen with some Type II2 (humic-sapropelic) components, suggesting a strong capacity for gas generation. Thermal maturity analysis revealed that the source rocks have reached the overmature dry gas stage, signifying advanced thermal evolution.DiscussionThe findings highlight the central and southern parts of the Yanchang gas field as promising exploration targets, characterized by high TOC content, favorable kerogen type indices, and high Ro values. These features collectively demonstrate the significant hydrocarbon generation potential of the Upper Paleozoic source rocks.ConclusionThe Upper Paleozoic coal-bearing source rocks in the Yanchang gas field represent a highly prospective target for natural gas exploration, particularly in regions with favorable organic geochemical properties.